Effects of cryopreservation on redox status and gene expression of trochophore larvae in Mytilus galloprovincialis. Issue 2 (9th October 2021) - Liu, Yibing; Catalano, Sarah R.; Qin, Jianguang; Han, Jiabo; Zhan, Xin; Li, Xiaoxu
Abstract: The relative mortality rate of trochophore larvae exposed to cryopreservation is significantly higher at early larval developmental stages in blue mussels Mytilus galloprovincialis . However, little is known about cryodamage on the larval quality at cellular and molecular modifications in aquatic species, including M. galloprovincialis . This study aimed to investigate the effects of established cryopreservation technique on reactive oxygen species (ROS), total antioxidant capacity, apoptotic and antioxidant enzyme related gene expressions of trochophore larvae in M. galloprovincialis . The results showed that significantly lower D‐larvae rate was produced from the cryopreserved trochophore larvae compared to fresh ( p <.05). Nevertheless, there was no significant difference in the ROS production, total antioxidant capacity, and small molecular antioxidant capacity between fresh and cryopreserved trochophore larvae ( p >.05). Similarly, the cryopreservation procedures had no adverse effects on the apoptotic and antioxidant enzyme related gene expression patterns between fresh and cryopreserved trochophore larvae ( p >.05). These results indicate that the cryopreservation technique applied to M. galloprovincialis larvae in this study may not compromise the redox status of the post‐thaw trochophore larvae.